MAINTENANCE ACTIVITY PLANNING FOR FUEL SYSTEM COMPONENTS ON KT-1B AIRCRAFT USING RELIABILITY METHODS - Adiksa, Ekklesia Christian; Setiawan, Ferry; Wicaksono, Dhimas; Anhar, Muh (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
This research aims to prevent unscheduled maintenance by determining the optimal maintenance time to plan preventive maintenance on the fuel system of the KT-1B aircraft. Fuel System components include Engine Driven Pump, Fuel Control Unit. The methods used are Fault Tree Analysis (FTA), Failure Mode and Effect Analysis (FMEA), and Weibull Distribution. This method is to determine the factors causing failure, calculate the failure rate, and system reliability. Factors causing fuel system failure are influenced by age, damaged seals, vibration. The level of reliability of the Fuel System decreases with the length of use. Where the system will experience a critical period when it reaches operational time, namely engine driven pump = 1010 hours with a reliability value of 70%, fuel control unit = 1637 hours with a reliability value of 70.1%. After knowing the critical mass limit of the components, Preventive Maintenance planning will be carried out on the parts and components that cause failure, namely by cleaning the engine driven pump components and the fuel control unit by periodically checking the parts on the KT-1B aircraft.